Periodontal pathology in rheumatic diseases: a prospective direction of interdisciplinary studies (Эндодонтия Today)
The paper presents evidence for a relationship between the periodontal disease (PD) and chronic autoimmune inflammatory response. PD is associated with systemic inflammation and vascular disease, which is characterized by endothelial dysfunction and significant risk of cardiovascular and cerebrovascular diseases, diabetes, autoimmune diseases, including rheumatoid arthritis. Further interdisciplinary research of various aspects of PD have prospects for rheumatic diseases.